The efficacy of a Lumbar Strengthening Program in Lumbar Spine Derangement Syndrome 1 - DR.DIVYA GOHIL; PROF REJI SAMUEL (International Journal of Pharma and Bio Sciences, 2018)
Low back pain is a condition that continues to place a great deal of a stress on a healthcare systems of a industrialized societies. This study aims to determine whether the inclusion of a strengthening program for the lumbar extensor muscles along with McKenzie therapy program is effective in the management of low back pain. 40 subjects were randomly divided into two treatment groups and were given Mckenzie exercises group A and the McKenzie exercises & performed Resistance Training for the Lumbar Extensors Muscles (RTLE) (group B). A significant reduction in the pain intensity (p<0.05), and increase in the functionality (p< 0.05) between pre & post treatment stages in both groups were found. Group B showed a more significant improvement when compared to Group A. McKenzie therapy with resistance training for lumbar extensors muscles produced a significantly greater decline in the pain intensity and improvement in function, when compared to Mckenzie exercises alone.